Thyroid metastasis from esophageal adenocarcinoma: a case report and literature review - Shinsei Yumoto; Yoshifumi Baba; Daichi Nomoto; Kazutaka Oozono; Kojiro Eto; Yukiharu Hiyoshi; Yohei Nagai; Masaaki Iwatsuki; Shiro Iwagami; Yuji Miyamoto; Naoya Yoshida; Yoshiki Mikami; et al. (Surgical Case Reports, 2019)
Abstract Background The incidence of metastatic spread of gastrointestinal malignancies to the thyroid gland is relatively low and most of these malignancies originate from the colorectum. Thyroid metastasis originating from the esophagus is poorly documented. Case presentation A 79-year-old man presented with hoarseness of voice and swallowing difficulty. Eighteen months earlier, he had undergone preoperative chemotherapy (S-1 and oxaliplatin [SOX] therapy) and subtotal esophagectomy with regional lymph nodes dissection and retrosternal narrow gastric tube reconstruction for advanced Barrett’s esophageal adenocarcinoma. In the ultrasonographic examination, there was a hypoechoic, indistinct border and heterogeneous nodule in the left lobe of the thyroid gland. Pathological examination of an ultrasound-guided fine-needle aspiration showed adenocarcinoma, supporting a diagnosis of esophageal adenocarcinoma metastases in the thyroid. Conclusion This is a first case of a patient with thyroid metastasis from Barrett’s esophageal adenocarcinoma after subtotal esophagectomy.